2023
DOI: 10.1002/alr.23228
|View full text |Cite
|
Sign up to set email alerts
|

Are you congested? A comparison of definitions between otolaryngologists and their patients

Abstract: ObjectiveTo assess for differences of intended meaning in the description of congestion‐related symptoms among otolaryngology patients and clinicians.Materials and MethodsBetween June 2020 and October 2022, a questionnaire consisting of 16 common descriptors of congestion‐related symptoms within four domains (obstructive‐related, pressure‐related, mucus‐related, and other symptoms) was completed by patients and otolaryngologists at five tertiary otolaryngology practices. The primary outcome was to assess diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Prior studies have demonstrated significant differences between patients and clinicians in the verbiage used to describe other common otolaryngologic complaints such as congestion, 7,8 reflux, 9 and sinus infections. 10,11 Dizziness has also been previously evaluated at a single institution, where there was found to be significant differences in how patients and clinicians define this common complaint.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have demonstrated significant differences between patients and clinicians in the verbiage used to describe other common otolaryngologic complaints such as congestion, 7,8 reflux, 9 and sinus infections. 10,11 Dizziness has also been previously evaluated at a single institution, where there was found to be significant differences in how patients and clinicians define this common complaint.…”
Section: Introductionmentioning
confidence: 99%